Jalal Hosseini Talabani's diplomatic activities with Iran from 2003 to 2013 - تاهیر, Prof.Dr.Pishko Hama Tahir Abdulrahman حه‌مه‌; مجید, م.م. ئازاد مجید محمد (Sulaimani Journal for Humanities, 2025)
The research titled (Diplomatic Activities of Jalal Hesamuddin Talabani with the Iraqi Regional Countries during 2003-2013, Iran as an example) explores the influential role and activities of Jalal Hesamuddin Talabani in rebuilding and strengthening Iraq's relations with regional countries, particularly Iran. Following the 2003 invasion of Iraq by the United States and its allies, Iraq urgently needed to establish diplomatic relations with neighboring countries after years of domestic political instability. Jalal Talabani recognized the importance of fostering these relationships, especially with prominent regional countries like Iran. Beginning in 2003, Talabani actively developed and maintained relations with Iran, continuing to do so until he fell ill at the end of 2012. His efforts had a lasting positive impact on the bilateral relations between Iraq and Iran, even after his departure from the political arena.
Keywords: Jalal Talabani; Diplomacy; Iraq; Iran; Regional States